Coupling between the Andes and the Amazon River Basin and their feedbacks with the Tropical North Atlantic and Tropical Pacific Ocean (2017)
IIn this thesis we study the hydroclimatic interrelations between the Andes and the Amazon River basin with the Tropical North Atlantic and the Tropical Pacific. Particularly, we estimate the separate and conjoint surface and atmospheric water budgets in the entire Amazon River basin, its major sub-catchments, as well as in the Andean and low-lying portions of the Amazon River basin. The water balances approach provided an update regarding the spatial patterns of the water budgets closure in the basin, and a quantification of the two-way interactions and coupling existing between the Andean and low-lying regions of Amazonia. We studied the complex two-way feedback dynamics between the Amazon River basin and the Tropical North Atlantic with linear and non-linear methodologies, and the analysis showed that at seasonal and interannual timescales the Amazon River basin plays an active role modulating the Tropical North Atlantic Sea Surface Temperatures. Finally, with the use of a new non-linear methodology we provided new insights of the function that the Amazon River basin plays in the connection between the Pacific Ocean and the Tropical North Atlantic during an El Niño event as “land-atmosphere” bridge.